GIS Model for Assessment of Land Use and Urban Development Effects on Stormwater Runoff: Puhinui Catchment Case Study - Krpo, Ana (Auckland University of Technology, 2004)
As local authorities are becoming more interested in the assessment of pollutant loads, this study offers a Geographic Information System (GIS) model for assessing nonpoint source of pollution for two scenarios: the current and ultimate stage of urbanization. The Puhinui Catchment, Manukau City, has been used as a case study in developing and testing this model. This catchment has all the attributes of a "typical" urban area and gives a good representation of the effects of land use on the receiving waters of Puhinui Stream and its estuary. Annual mass contaminant loadings were calculated by firstly assessing the physical characteristics of the Puhinui catchment (case study catchment) and secondly describing the nature of storm water quality and calculating the annual mass contaminant loadings.GIS is used to multiply the annual runoff volume by a mean pollutant concentration to acquire an average annual pollutant load. The annual runoff volume is calculated from the drainage area, runoff coefficient and annual rainfall. To calculate the total mean pollutant load, the pollutant loads for all land use types within the catchment are summed and the process is applied for each pollutant. This GIS model determines the connection of typical pollutant concentrations with land uses in the catchment and offers a characterisation of nonpoint source pollution in that catchment. This model can be used for, identifying catchment areas that contribute considerably to the pollution of waterways, determining the appropriate treatment of the storm water runoff for particular sub catchment, storm water quality improvement prioritization and cost-benefit analysis, selecting locations for water-quality monitoring stations, improvement in maintenance practices, assessment of proposed development environmental effects.
Keywords: Geographic information systems; Urban runoff; Storm sewers; Water; Pollution; Enviornmental studies